Cave millipeds of the United States. X. New species and records of the genus Pseudotremia Cope. 2. Species from Virginia, USA (Diplopoda, Chordeumatida, Cleidogonidae) - Shear, William A. (Zootaxa, 2011)
The milliped genus Pseudotremia Cope 1869 as it occurs in Virginia, USA, is reviewed, with new records and species, mostly from caves. Seventeen new species, Pseudotremia loomisi, P. contorta, P. cerberus, P. pomarium, P. orndorffi, P. peponocranium, P. glaber, P. fergusoni, P. jaculohamatum, P. fremens, P. hubbardi, P. ryensis, P. piscator, P. culveri, P. salfodina, P. johnholsingeri and P. inexpectata are described, for a total Virginia fauna of 25 species. Additional species are predicted to occur. New locality records are given for seven previously described species, Pseudotremia alecto Shear 1972, P. hobbsi Hoffman 1950, P. sublevis Loomis 1944, P. tuberculata Loomis 1939, P. momus Shear 1972, P. nodosa Loomis 1939, and P. valga Loomis 1943. Taxonomic characters useful in delimiting species of Pseudotremia are discussed.